Xingxiao Pill Suppressed the Progression of Non-Small Cell Lung Cancer by Targeting SREBP1/FASN–Induced Fatty Acid Biosynthesis via PI3K/AKT/mTOR Signaling Pathway - Zhou X; Hu X; Zhang Z; Lin S; Lin X; Zhou T; Bai Y; Hu K (Cancer Management and Research)
Xiangnan Zhou,1,2,* Xiuhua Hu,2,3,* Zhiying Zhang,2,* Shicheng Lin,2 Ximing Lin,2 Tian Zhou,2 Yanping Bai,1 Kaiwen Hu2 1Department of Dermatology, China-Japan Friendship Hospital, National Center for Integrated Traditional Chinese and Western Medicine, Beijing, 100029, People’s Republic of China; 2Department of Oncology, East Hospital, Beijing University of Chinese Medicine, Beijing, 100078, People’s Republic of China; 3School of Life Sciences, Beijing University of Chinese Medicine, Beijing, 102488, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanping Bai, China-Japan Friendship Hospital, National Center for Integrated Traditional Chinese and Western Medicine, Beijing, 100029, People’s Republic of China, Email yanpbCJFH@163.com Kaiwen Hu East Hospital, Beijing University of Chinese Medicine, Beijing, 100078, People’s Republic of China, Email kwhbucm@163.comIntroduction: Xingxiao Pill (XXP), a typical traditional Chinese medicine (TCM) prescription drug used to treat NSCLC in clinic. However, the mechanism underlying its regulatory effects remains unclear. This study aimed to evaluate the potential efficacy of XXP in treating NSCLC and to investigate how XXP regulates fatty acid biosynthesis in NSCLC.Methods: A lung carcinoma mouse model was created by transplanting Lewis lung carcinoma (LLC) cells into male C57BL/6 mice. Lung cancer cell models using LLC and A549 cells were also constructed. XXP’s therapeutic efficacy on NSCLC was assessed via oral gavage. Bioinformatics analysis and transcriptome sequencing identified XXP’s potential targets and mechanisms. These findings were verified by in vitro cell assays, Western blotting, immunofluorescence staining, and Oil Red O staining.Results: XXP inhibited lung tumor growth, suppressed cell proliferation and impeded cell migration. Additionally, it influenced the processes of apoptosis and cell cycle in both A549 and LLC cells. Bioinformatics analysis suggested that regulation of fatty acid biosynthesis and phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway were crucial mechanisms underlying the antitumor effects of XXP in lung cancer. XXP reduced the levels of the fatty acid biosynthesis products, such as total cholesterol (TC), triglycerides (TG), lipids, and free fatty acids in A549 cells, and downregulated the expression of sterol regulatory element binding protein 1 (SREBP1) and fatty acid synthase (FASN). Furthermore, XXP decreased the expression level of PI3K, AKT, mTOR, phospho–PI3K, and phospho–AKT.Discussion: XXP exerts its inhibitory effect on lung cancer tumor growth by controlling the biosynthesis of fatty acids and the PI3K/AKT/mTOR signaling pathway. The research suggests that targeting this metabolic pathway could be a viable strategy for cancer therapy and emphasizes the value of TCM in providing a rich source of innovative pharmaceuticals for cancer treatment. Keywords: Xingxiao Pill, PI3K/AKT/mTOR pathway, fatty acid biosynthesis, lung cancer, SREBP1, FASN